AZV Dinner Malam Nostalgia,11 August 2023: Raia Hotel, Kuching / Nur Atiqah Husaini ... [et al.] - Husaini, Nur Atiqah; Hamzah, Hanisah Aimi; Abdul Rahman, Abdul Ruqaim Ashraff; Aziz, Syazwani Aqmar (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
On the 11th August 2023, the Annual AZV dinner was held at Raia Hotel, Kuching. The event started at 7pm and hosted by the final year student, Classix studio to appreciate every AZV members and lecturers. With the theme of nostalgia, all students dressed up with clothings from the 60’s to the 90’s. During the event, a montage was played reminiscing the old days from the first year of Classix studio until their final year. A song was performed by the AZV Buskers and a special performace by Classix’s part time design lecturer Mr. Mohd Affrizan. The dinner was attended by all full time and part time lecturers that had taught Classix studio during their final year of studies. Queen and King of the night was won by Nurshafina of Classix Studio and Hariz Farhan of Classix Studio while Best Dress and for lecturer was won by Madam Izzati Sebri. The event ended at 11pm with group photos and studio photos session.